Influence of macro-topography on mechanical performance of 1.0 wt% nanoclay/multi-layer graphene-epoxy nanocomposites. (August 2017) - Atif, Rasheed; Inam, Fawad
Influence of topography on the variation in mechanical performance of 1.0 wt% multi-layer graphene (MLG)/nanoclay-epoxy samples has been investigated. Three different systems were produced: 1.0 wt% MLG-EP, 1.0 wt% nanoclay-EP, and 0.5 wt% MLG-0.5 wt% nanoclay-EP. The influence of synergistic effect on mechanical performance in case of hybrid nanocomposites is also studied. Various topography parameters studied include maximum roughness height (Rz or Rmax ), root mean square value (Rq ), roughness average (Ra ), and surface waviness (Wa ). The Rz of as-cast 1.0 wt% multi-layer graphene, nanoclay, and 0.5 wt% MLG-0.5 wt% nanoclay-EP nanocomposites were 41.43 µm, 43.54 µm, and 40.28 µm, respectively. The 1200P abrasive paper and the velvet cloth decreased the Rz value of samples compared with as-cast samples. In contrary, the 60P and 320 P abrasive papers increased the Rz values. Due to the removal of material from the samples by erosion, the dimensions of samples decreased. The weight loss due to erosion was commensurate with the coarseness of abrasive papers. It was recorded that multi-layer graphene is more influential in enhancing the mechanical performance of epoxy nanocomposites than nanoclay. Additionally, it was observed that mechanical performance of hybrid nanocomposites did not show a marked difference suggesting that synergistic effects are not strong enough in multi-layer graphene and nanoclay.